The Subordinated of Tomorrow. Croatian Dystopian Prose in the Postcolonial Approach - Wojtaszek, Aleksandra (Porównania, 2016)
In the Croatian literature, which since the collapse of Yugoslavia has been dominated mainly by neo-realistic trends, over the past few years the rapid growth of popularity of dystopia – a genre which until now almost did not occur – can be observed. The means used in the work of fiction allow for representation of the present-day negative trends at the system level, without the need to present individual epiphenomena. Methodological tools, used for the analysis of the literature presented in this article, are provided by the postcolonial reflection, and the key operational tools used in the proposed interpretation of the Croatian dystopian fiction are categories of exclusion, subordination and authority, derived directly from the philosophy of Michel Foucault and the works of his continuator – Giorgio Agamben, as well as the issues connected to the relations and deep divisions between the center and the peripheries, the epistemic violence and the post-colonial discourse.